Historical Refugia and Isolation by Distance of the Mud Snail, Bullacta exarata (Philippi, 1849) in the Northwestern Pacific Ocean - Shi, Lu-Ye; Li, Jia; Wu, Shu-Qing; Han, Jie (Frontiers in Genetics, 2018)
Many phylogeographic studies on marine organisms in the northwestern Pacific have supported for the biogeographic hypotheses that isolation in the marginal seas of this region during the Pleistocene glaciation lower sea level led to population genetic divergence, and thus population expansion was a common phenomenon when the sea level rebounded. However, most of these studies were based on maternally inherited mitochondrial DNA markers with limited sample sites and therefore, were unable to reveal detailed pictures encompassing paternal line information covering of the entire range. In this study, we used the mitochondrial cytochrome c oxidase subunit I (COI) and nine nuclear microsatellite loci to investigate the phylogeography of the mud snail, Bullacta exarata (Philippi, 1849), a species endemic to the northwestern Pacific. We sampled 14 natural populations spanning across 3800 km of the Chinese coastline, essentially covering most of the species distribution range. COI analysis identified a total of 149 haplotypes separated into two distinct groups with nine mutation steps, revealing a prominent phylogeographic structure. Nuclear microsatellite data also demonstrated a similar but weaker genetic structure. The estimated time to the most recent common ancestor between the two COI haplogroups is at 0.89 Ma, indicating that B. exarata populations survived the Pleistocene glaciation in the Sea of Japan and the Okinawa Trough, two marginal seas around the species range. The consistent significant patterns of isolation by distance of both COI and microsatellites suggests that limited mobility of adults and short planktonic stage of larvae may have played an important role in promoting or maintaining the genetic differentiation of B. exarate. Results from population demographic analyses support population expansion late in the Pleistocene era.